Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have a matrix $A$ and I introduce $(I+A)^{m},$ where $I$ is the identity matrix of same order with $A$ and $m$ is a positive integer. I want to show that if $(1+ \lambda )^m$ is a simple eigenvalue of $(I+A)^m$, that is, it is not a repeated root of the characteristic polynomial of $(I+A)^m,$ then $ \lambda$ is a simple eigenvalue of $A.$ Any help with this will be highly appreciated.

Edit: what I mean by a simple eigenvalue.

For an arbitrary matrix $A$ of order $n \times n,$ let $ \lbrace \lambda_1,\lambda_2,\lambda_3, \dots ,\lambda_k \rbrace $ be the set of distinct eigenvalues of $A.$ The characteristic polynomial of $A,$ denoted $p(\lambda),$ can be written in the factorized form \begin{equation} p(\lambda) = (\lambda_1-\lambda)^{n_1}(\lambda_2-\lambda)^{n_2} \dotsm (\lambda_k-\lambda)^{n_k}\end{equation} with $n_1+n_2+ \dotsm +n_k = n.$ The exponent $n_i,$ corresponding to each eigenvalue $\lambda_i,$ is called the algebraic multiplicity of $ \lambda_i$ and the dimension of the null space of $ A - \lambda_i I, \dim(N(A - \lambda_i I )),$ is called the geometric multiplicity of $ \lambda_i.$ If $n_i=1$ for some $i \in \lbrace 1, 2, \dots, k \rbrace,$ then $ \lambda_i$ is said to be a simple eigenvalue of $A.$

share|improve this question
1  
The $I+A$ is purely ornamental here ; your question can be rephrased equivalently (and more simply) as : show that if $\mu^m$ is a simple eigenvalue of $B^m$, then $\mu$ must be a simple eigenvalue of $B$. –  Ewan Delanoy Jan 5 '13 at 12:59
add comment

3 Answers 3

up vote 2 down vote accepted

Here is the “algebraic” version of Ofir’s answer.

In that case also, it is easier to show the contraposite : if $\lambda$ is a repeated ALGEBRAIC eigenvalue of $A$, then $(1+\lambda) ^m$ is a repeated ALGEBRAIC eigenvalue for $(I+A)^m$.

So suppose that $\lambda$ is a repeated algebraic eigenvalue of $A$. The matrix $B=A-\lambda I$ has determinant zero, so its kernel is nontrivial : there is a nonzero $v_1$ such that $Bv_1=0$. Let $C$ be the lower rightmost $(n-1)\times(n-1)$ square submatrix of $A$ defined by $C=(c_{ij})_{1 \leq i ,j \leq n}$ with $c_{ij}=a_{i+1,j+1}$. Then $\chi_A(t)=(t-\lambda)\chi_C(t)$ where $\chi$ denotes the characteristic polynomial. We deduce that $\lambda$ is also an eigenvalue of $C$, so there is a $v_2$ independent from $v_1$ such that $Cv_2=0$. Therefore $Bv_2$ is of the form $cv_1$, for some constant $c$ : in other words $Av_1=\lambda v_1$ and $Av_2=\lambda v_2+cv_1$.

So $$ A^2v_2=A(\lambda v_2+cv_1)=\lambda Av_2+cAv_1=\lambda^2v_2+(2c\lambda)v_1 \tag{1} $$ More generally, we have by induction that $A^kv_2=\lambda^kv_2+(ck\lambda^{k-1})v_1$ for any $k\geq 0$. It follows that

$$P(A)v_2=P(\lambda)v_2+c\frac{\partial P}{\partial \lambda}(\lambda)v_1 \tag{2} $$ for any polynomial $P$.

Completing the pair $(v_1,v_2)$ in a basis $(v_1,v_2, \ldots ,v_n)$ of ${\mathbb K}^n$, and working in this new basis, we see that $P(A)$ is of the form

$$ P(A)=\left( \begin{array}{ccl} P(\lambda) & c\frac{\partial P}{\partial \lambda}(\lambda) & \ldots \\ 0 & P(\lambda) & \ldots \\ \mathbf O & \mathbf O & \ldots \\ \end{array} \right) $$

So $P(\lambda)$ is always a repeated algebraic eigenvalue of $P(A)$, for any polynomial $P$.

share|improve this answer
add comment

EDIT: This solution is wrong, as shown in the comments.

In general, $Av=\lambda v \implies p(A)v=p(\lambda)v$ for any polynomial $p$. This implication shows that the multiplicity of $p(\lambda)$ is at least the multiplicity of $\lambda$, since any eigenvector of $\lambda$ translates to an eigenvector of $p(\lambda)$. One consequence is that if $p(\lambda)$ is simple, $\lambda$ must also be simple. (Assuming $\lambda$ is an eigenvector of $A$.)

In your case, $p(x)=(1+x)^m$.

Proof of $Av=\lambda v \implies p(A)v=p(\lambda)v$: By linearity, it is enough to prove for $p(x)=x^k$. This follows my applying $A$ to both sides of $Av=\lambda v$ $k-1$ times.

share|improve this answer
    
My understanding is that the implication, mentioned in the first line, shows that the geometric multiplicity of $p( \lambda)$ is at least the geometric multiplicity of $ \lambda.$ But simple eigenvalue is defined by the algebraic multiplicity, so how could we get the consequence that if $p( \lambda)$ is a simple, $\lambda$ must also be simple? –  Zizo Jan 5 '13 at 12:06
    
@Zizo : you would do well to edit your original post and explain those geometric/algebraic subtleties. I think most people understood your question the way Ofir did, which is not what you intended. –  Ewan Delanoy Jan 5 '13 at 12:50
add comment

As someone (I forgot who) pointed out in a deleted answer, your statement, as it stands, is false. Although every eigenvalue $\lambda$ of $A$ gives rise to an eigenvalue $(1+\lambda)^m$ of $(I+A)^m$, the converse is not true because the mapping $\lambda\mapsto(1+\lambda)^m$ is not one-to-one. For instance let $A=-3,\ \lambda=1$ and $m=2$. Then $(1+\lambda)^2=4$ is an eigenvalue of $(I+A)^2=4$, but $\lambda=1$ is not an eigenvalue of $A=-3$.

So, assume that $\lambda$ is an eigenvalue of $A$. Let $v$ be a corresponding eigenvector. By a change of basis, we may assume that $A$ and $(I+A)^m$ are of the form $$ A=\begin{pmatrix}\lambda&u^T\\0&C\end{pmatrix}, \ (I+A)^m=\begin{pmatrix}(1+\lambda)^m&v^T\\0&(I+C)^m\end{pmatrix}, $$ where $C$ is an $(n-1)\times(n-1)$ matrix. Since $\det(xI-A)=(x-\lambda)\det(xI-C)$, if $\lambda$ is a repeated eigenvalue of $A$, it must be an eigenvalue of $C$ and hence $1+\lambda$ is a repeated eigenvalue of $(I+C)^m$, thus making $(1+\lambda)^m$ a repeated eigenvalue of $(I+A)^m$, which is a contradiction.

share|improve this answer
    
Great! could you explain a contradiction with what? –  Zizo Jan 6 '13 at 15:46
    
@Zizo A contradiction to the assumption that $(1+\lambda)^m$ is a simple eigenvalue of $(I+A)^m$. –  user1551 Jan 6 '13 at 16:39
    
I wanted to know that if $(1+ \lambda)^m$ is a simple eigenvalue of $(I+A)^m,$ then $ \lambda$ is a simple eigenvalue of $A$ which you did show using a contrapositive argument, that is, if $ \lambda$ is repeated eigenvalue of $A, (1+ \lambda)^m$ is repeated eigenvalue of $(I+A)^m.$ –  Zizo Jan 7 '13 at 2:23
    
@Zizo Exactly. So we have a proof for your statement, haven't we? –  user1551 Jan 7 '13 at 8:22
    
YES. \=D/ .. THANKS. –  Zizo Jan 7 '13 at 8:57
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.